Values and their relationship to social problems in Malaysia: an Islamic framework - Haneef, Mohamed Aslam; Selamah , Abdullah Yusof; Mohd. Amin, Ruzita; Md. Noon, Hazizan (Association of Muslim Social Scientists, 2002)
This study analyzes the relationship between values and socialproblems for Malaysian teenagers. Malaysia has undergone a tremendous social transformation that has affected many of its traditional and religious values and norms. This development is said to have contributed to a rise in social problems. Our basicpremises are that values are reflected by behavior and that religion plays an important role in Malaysians’ value formation. In this context, and since Islam is Malaysia’s official religion, the measurement of values is based on the works of al-Ghazali and Rokeach.1 Some suggestions also are provided for future development policies.